(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study examines to measurement impact of savings in economic growth in Sudan during the period from 1990-2013. This study aimed to know the Real factors that affect economic growth. The study follows the descriptive statistical and analytical add econometrics analysis formulation, descriptive, estimate and forecasting the econometrics model. The study reached a number of the most important results: there was an inverse relationship between consumption and economic growth in Sudan. The study recommends the development and support of the private sector and increases production and productivity, increasing the endogenous capacity of the Sudanese economy to finance domestic savings and ignoring the grants and foreign loans to finance development.